ANALISIS KEBERLANJUTAN USAHATANI KOPI SERTIFIKASI COMMON CODE FOR THE COFFEE COMMUNITY (4C) DI KABUPATEN TANGGAMUS PROVINSI LAMPUNG - Gita Marindra; Bustanul Arifin; Yaktiworo Indriani (Lampung University, 2018)
This research aims to analyze farming income and sustainability of farming practices of coffee certification farmers and coffee non-certification farmers in Tanggamus Regency. This research used survey method. The numbers of samples in this research were 44 respondents of certification farmers and 24 respondents of non-certification farmers. The data was collected from August 2017 to November 2017. The data was analyzed by quantitative and qualitative descriptive analysis. The results showed that farming income of certification farmers were higher than non-certification farmers. Socially and environmental sustainable farming practices of certification farmers were more sustainable than non-certification farmers. Sustainability of economy, social and environmental aspects of certification farmers were more sustainable than non-certification farmers. Total of farming income of certification farmers and non-certification farmers were Rp16,330,309 per hectare and Rp10,637,482 per hectare. About 93.20% of certification farmers’s farming were sustainable, while about 91.70% of non-certification farmers’s farming were quite sustainable. Key words: certification, coffee, farming, sustainability